2016
DOI: 10.1017/jsl.2015.54
|View full text |Cite
|
Sign up to set email alerts
|

Stable Canonical Rules

Abstract: Abstract. We introduce stable canonical rules and prove that each normal modal multi-conclusion consequence relation is axiomatizable by stable canonical rules. We apply these results to construct finite refutation patterns for modal formulas, and prove that each normal modal logic is axiomatizable by stable canonical rules. We also define stable multi-conclusion consequence relations and stable logics and prove that these systems have the finite model property. We conclude the paper with a number of examples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 29 publications
(38 reference statements)
1
41
0
Order By: Relevance
“…This provides an intuitionistic analogue of similar results in [6]. Our proofs are modifications of those in [6,Sec. 5] and generalize those in [5,Sec.…”
Section: (∧ ∨)-Canonical Rulessupporting
confidence: 64%
See 1 more Smart Citation
“…This provides an intuitionistic analogue of similar results in [6]. Our proofs are modifications of those in [6,Sec. 5] and generalize those in [5,Sec.…”
Section: (∧ ∨)-Canonical Rulessupporting
confidence: 64%
“…The (∧, ∨)-canonical rules are the intuitionistic counterpart of the stable canonical rules of [6], and are an alternative of Jeřábek's canonical multi-conclusion rules [21]. We also indicate how to generalize (∧, →)-canonical formulas to (∧, →)-canonical rules, which provide another uniform axiomatization of all intuitionistic multi-conclusion consequence relations.…”
Section: Introductionmentioning
confidence: 98%
“…e.g. [25,26]) but modal logicians usually focus on properties of filtrations that do not play a role in learning. Closely related to this question is a more diagrammatic understanding of termination and correctness of our algorithm: we believe that all essential ingredients for this are contained in our work but we need to understand filtrations on a more abstract, categorical level.…”
Section: Discussionmentioning
confidence: 99%
“…Stable homomorphisms were considered in [3] under the name of semi-homomorphisms and in [13] under the name of continuous morphisms. We now come to stable canonical rules: It was proved in [1] that every multi-conclusion consequence relation above K is axiomatizable by stable canonical rules (relative to arbitrary finite modal algebras -not only to those validating K4-axiom). The same proof can easily be extended to our multi-conclusion consequence relations above K4.…”
Section: It Is Easy To See That H : a → B Is Stable Iff H( A) ≤ H(a)mentioning
confidence: 99%
“…Our goal is to establish the same property for stable multi-conclusion canonical rules for IPC, K4, and S4. These rules were recently introduced in [1], where it was shown that each normal modal multi-conclusion consequence relation is axiomatizable by stable multi-conclusion canonical rules. The same result for intuitionistic multi-conclusion consequence relations was established in [2].…”
Section: Introductionmentioning
confidence: 99%